O Lúdico como estratégia para o ensino das habilidades do manejo em cadeira de rodas em um programa de reabilitação - Pimentel, Beatriz Bentes (Brasil, 2025)
This research aimed to present an intervention program in physical rehabilitation based on the use of play as a strategy for teaching HMCR to a child with spinal cord injury. This is a descriptive and exploratory case study. The context of the research was in the Motor Activities Program for the Disabled (PROAMDE), at the Getúlio Vargas University Hospital (HUGV). The participant was an eight-year-old child with paraplegia, who underwent rehabilitation at PROAMDE in 2022. Data collection was carried out from the PROAMDE/HUGV medical records database. Intervention plans were used, as well as the patient's initial and final assessments. Data analysis was carried out in a descriptive way, with analysis categories being formed a priori based on the teaching stages of the aforementioned skills. Subsequently, the data were discussed in light of the literature review. In the rehabilitation program investigated, the HMCR were divided into stages with the aim of allowing them to be worked on progressively, facilitating understanding and learning. The development stages were as follows: touching the chair, moving forwards, backwards, sideways and zigzagging, going up and down ramps, prancing the CR while still and going up and down steps. This allowed each skill to be developed gradually. The game was an ally in the teaching process, allowing the child to effectively engage in the intervention protocol. In the HMCR evaluated, the patient progressed from the result “does not perform” or “performs with difficulty” in the initial assessment to “performs” in the final evaluation. This research highlighted the importance of play as a strategy for teaching HMCR to a child in a physical rehabilitation program. The results described reinforce the importance of playful approaches during care, providing a new meaning to the environment and greater assertiveness in care protocols.